Stability of hybrid rice genotypes for grain yield and maturity - Hasan, MJ; Kulsum, MU; Hossain, E; Rahman, NMF (Bangladesh Journal of Agricultural Research, 2018)
An experiment was conducted using nine hybrid rice genotypes along with two inbred standard check varieties in five different locations of Bangladesh to assess their stability in terms of grain yield and maturity in diverse environments. For this, adaptability, stability, genotype × environment (G×E) interaction effect for grain yield and maturity of 11 rice varieties in five agro ecological zones in Bangladesh were assessed during T. Aman season of 2015. The analysis of variance for growth duration and grain yield (t/ha) for genotypes, environment and genotype-environment interaction were highly significant at 1% level of probability indicating the variable response of genotypes and environments. The hybrid genotypes IR79156A/BRRI20R, BRRI hybrid dhan3, BRRI33R/BRRI26R, BRRI hybrid dhan4, standard check variety BRRI dhan49 and BR11 had high yield performance and widely adapted to all environments and these were non sensitive to environmental interactive forces, while the hybrids BRRI7A/BRRI31R, IR79156A/BasmatiR and SL-8 were sensitive to environmental interaction. Environment such as Gazipur (E1) and Faridpur (E3) having positive IPCA1 score and positive interaction with the hybrids BRRI7A/BRRI13R, SL-8H and IR79156A/BasmatiR were considered as the favourable environments for these hybrids. Bangladesh J. Agril. Res. 43(1): 99-108, March 2018